KAJIAN PERANCANGAN RUANG KOMUNITAS SENI SKETSA PERJALANAN JAKARTA - Andrew Christian Widjaja; Sutarki Sutisna (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2019)
Milenials, especially in the capital city of Jakarta, stories of experience and travel in one place will not forget that moment to be immortalized, become a milenial lifestyle, until unwittingly the devoted moment is only for pleasure and selfishness, to forget the existing characteristics and culture in the place that is being visited. Indonesia is one of the countries that has a growing tourism sector that is currently high with the characteristics, culture and natural resources that exist. So that the government increases the economy from the tourism sector. One example is the capital city of Jakarta, the city of Jakarta in addition to being the administrative center of the country, it also has a very strong history and background, but often it is forgotten. Travelsketch community is a sketch art community that documents an event using sketches. This community documentation activity aims to study and observe existing cultures and expressions. The purpose of this design is to form patterns of interaction space that are in accordance with the character of travelsketch and milenials and how the milenial generation can be interested in getting to know the culture and character of a place. In the process of designing the pattern of space characteristics of travelsketch and regional patterns in Kota Tua, Jakarta  become the basis for forming a concept of space, so that the design is built in harmony with Kota Tua area. The Jakarta Travel Sketch Art Community is designed to introduce culture and character to a place through a sketch art, so that this community can become a venue for performances and education that shares experiences when in a place. Through this design the introduction of characteristics and tourist visitors that exist in a place can increase. AbstrakGenerasi Milenial terutama di Ibu Kota Jakarta  cerita pengalaman dan perjalanan di suatu tempat tidak akan lupa momen tersebut untuk diabadikan, menjadi sebuah gaya hidup milenial, hingga tanpa disadari momen yang diabdikan tersebut hanya untuk kesenangan dan keegoisan diri sendiri, hingga melupakan karakteristik dan kebudayaan yang ada di tempat yang sedang dikunjungi. Indonesia merupakan salah satu negara yang memiliki pertumbuhan parwisata yang sedang tinggi saat ini dengan karakteristik, kebudayaan dan kekayaan alam yang ada. Sehingga pemerintah meningkatkan perekonomian dari sektor pariwisata. Salah satu contohnya Ibu Kota  Jakarta, kota Jakarta selain menjadi pusat adminstratif negara, juga memiliki sejarah dan latar belakang yang sangat kuat, namun seringkali hal tersebut di lupakan. Komunitas Travelsketch merupakan sebuah komunitas seni sketsa yang mendokumentasi suatu kejadian dengan menggunakan sketsa. Kegiatan dokumentasi komunitas ini bertujuan untuk mempelajari dan mengamati kebudayaan yang ada dan untuk berekspresi. Tujuan dari rancangan ini adalah untuk membentuk pola ruang interaksi yang sesuai dengan karakter travelsketch dan milenial dan bagaimana generasi milenial dapat tertarik untuk mengenal kebudayaan dan karakter suatu tempat. Dalam proses perancangan pola ruang karakteristik travelsketch dan pola kawasan di Kota Tua menjadi dasar membentuk sebuah konsep ruang, sehingga rancangan yang di bangun selaras dengan kawasan Kota Tua. Komunitas Seni Sketsa Perjalanan Jakarta ini di rancang untuk memperkenalkan kebudayaan dan karakter suatu tempat  melalui sebuah seni sketsa, sehingga komunitas ini dapat menjadi sebuah wadah pertunjukan dan edukasi yang membagikan pengalaman ketika berada di suatu tempat. Melaui rancangan ini pengenalan karakteristik dan pengunjung  wisata yang ada di suatu tempat dapat meningkat.